Cytocompatibility Analysis of in vitro Pulverized Endodontic Files - Giuliana Soimu; Gabriela Cristina Carvalho da Silva; Viviane Oliveira Freitas Lione; Danielle Dutra Voigt; Fabiano Luiz Heggendorn (Journal of the California Dental Association)
Introduction A major problem in endodontic practice is fractured endodontic files. Such occurrences may predispose to periradicular infection, resulting in treatment failure. Several techniques are used to remove the metallic fragment, but none are completely safe. This study aimed to determine, in vitro, whether pulverized endodontic files caused cytotoxicity in L929 and VERO cell lines, according to the guidelines established by ISO 10,993-5:2009.Materials and Methods Forty endodontic files, #35 and #40, Kerr-type, Maillefer (Dentsply, Tulsa, OK, US), were pulverized and distributed in increasing concentrations to determine the cytotoxicity index (IC50) of metallic particles, by using the methyl-thiazol-diphenyl-tetrazolium (MTT) test.Results In the VERO cell line the different concentrations of pulverized files ranged from moderately cytotoxic in the 25 µg L. Pulv (72.59% IC50) and 50 µg L. Pulv (59.04% IC50) groups, to slightly toxic in the groups of 5 µg L. Pulv. (87.1% IC50) and 10 µg L. Pulv. (80.52% IC50). In the L929 cell line, exposure of 5 and 10 µg. of pulverized files demonstrated a nontoxic effect, with 100% cell viability. The concentration is 25 µg/l. Pulv. showed moderate cytotoxicity (55.55% IC50) and a concentration of 50 µg/l. Pulv. revealed to be severely cytotoxic (29.96% IC50).Conclusions Increasing concentrations of metallic particles produce reduction in the cell viability, categorized as cytotoxic at concentrations of 50 µg. This suggests that separated endodontic files can cause undesirable cytotoxic effects in the periapical tissues, leading to local inflammatory processes. This may encourage clinical practitioners to remove these instruments from the root canal system and develop new strategies to achieve this goal, thereby improving the success rates of root canal treatments.